Expression-Enhanced Fluorescent Proteins Based on Enhanced Green Fluorescent Protein for Super-resolution Microscopy - Duwé, Sam; De Zitter, Elke; Gielen, Vincent; Moeyaert, Benjamien; Vandenberg, Wim; Grotjohann, Tim; Clays, Koen; Jakobs, Stefan; Van Meervelt, Luc; Dedecker, Peter (ACS nano, 2015)
“Smart fluorophores”, such as reversibly switchable fluorescent proteins, are crucial for advanced fluorescence imaging. However, only a limited number of such labels is available, and many display reduced biological performance compared to more classical variants. We present the development of robustly photoswitchable variants of enhanced green fluorescent protein (EGFP), named rsGreens, that display up to 30-fold higher fluorescence in E. coli colonies grown at 37 °C and more than 4-fold higher fluorescence when expressed in HEK293T cells compared to their ancestor protein rsEGFP. This enhancement is not due to an intrinsic increase in the fluorescence brightness of the probes, but rather due to enhanced expression levels that allow many more probe molecules to be functional at any given time. We developed rsGreens displaying a range of photoswitching kinetics and show how these can be used for multimodal diffraction-unlimited fluorescence imaging such as pcSOFI and RESOLFT, achieving a spatial resolution of ∼70 nm. By determining the first ever crystal structures of a negative reversibly switchable FP derived from Aequorea victoria in both the “on”- and “off”-conformation we were able to confirm the presence of a cis–trans isomerization and provide further insights into the mechanisms underlying the photochromism. Our work demonstrates that genetically encoded “smart fluorophores” can be readily optimized for biological performance and provides a practical strategy for developing maturation- and stability-enhanced photochromic fluorescent proteins.